Improvement of Mushroom Business Management Technique - Heri Sulistiyono; Muazar Habibi; Yayuk Andayani; H Sudirman; A.J. Fathiyyah; Zakee Niseng (Unram Journal of Community Service, 2025)
Sembalun Bumbung Village faces significant challenges in maintaining a stable food supply and achieving economic resilience due to its location in a disaster-prone area. The region is at risk, making it dangerous to clear new land for agricultural cultivation. To address these issues, the Sembalun Mushroom Initiative aims to enhance food security and disaster resilience in the village by improving the quality of mushroom products and providing support in business management. The cultivation of straw mushrooms presents an alternative agricultural development that can support food security and boost the local economy. The advantages of straw mushroom cultivation include the fact that it does not require clearing new land or forests, and it typically yields good market prices. However, farmers in Sembalun Bumbung Village currently lack the knowledge and technology necessary to produce high-quality straw mushrooms and manage their businesses effectively. To help overcome these challenges, a community service team from the University of Mataram is assisting with advanced cultivation technology and business management practices. Their efforts include developing training programs that cover business management, marketing strategies, and resource management.